Teaching is a human interaction : how thoughtful educators respond, are responsive, and take responsibility - Jones, Alexis L. (Studies in the philosophy of education., 2023)
"This book contains an argument supported by education philosophers and my own composite stories, data, and experiences. I mention a number of scholars (e.g., Benjamin, 1988; Buber, 1970; Noddings, 2005, 2013; Palmer, 1983; van Manen, 1986, 1991, 2000) who address important human issues in the field of education, and I do my best to tie their work and my own together to show common themes within the issues of care, responsivity, and relational ethics. The first part of the book (Introduction and Chapters 1-3) is primarily philosophical, and I share the thoughts of the aforementioned scholars and others on topics relating to the very human work teachers do. In Chapter 1, I address what most of the public believes teachers' work is all about: caring about their students. However, caring for and about students are two different things, and while every teacher candidate is well primed to answer the interview question, "Why teaching?" with, "I just love children," the concept of caring and what this type of relational work does to teachers is more complex. Chapter 2 follows this with a description of relational ethics and what is missing from some of the more recent empirical work on student-teacher relationships; namely, that the relationship is not a means to an end. The relationship is an a means and an end in itself. Finally, Chapter 3 addresses how this relational work impacts our (very white and female) profession's attempts to often be nice more than we are kind. The concept of kindness is one that involves feeling with and for our fellow human beings, and at times, in our desire to be objective and professional, we lose some of our humanity in the classroom. The next section of the book (Chapters 4-6) combines theoretical works and empirical data to address the complexity and humanity of teaching. Chapter 4 is about the often contradictory but ubiquitous nature of working with humans: We must consider one another as we are now and also as we are growing and developing. These ideas of Buber's and van Manen's are at the heart of responsive teaching, as teachers consider the growing intellectual and emotional needs of their students while also focusing on the fact that a very vulnerable human is addressing them in the moment. Chapter 5 focuses on four very specific mindsets and actions responsive teachers embody: the type of noticing that takes place in responsive classrooms, the attunement necessary for humans to work sensitively with one another, recognition as the way we respond to one another in meaningful ways, and finally the seeing and being seen that is done when teachers establish a very humanistic classroom environment. Chapter 6 furthers this discussion on responsiveness, as we look at very real classroom examples of how teachers, once confronted with a spoken or unspoken need by their students, must respond. While the work described in the aforementioned chapters may appear to present an idea of ethical teacher perfection, this is not the case. Teachers are not supposed to be, nor are they logistically able to be, all things to all children. The final chapter instead addresses how stakeholders (e.g., educators, administrators, parents) can gently move our traditional education system toward this ideal. This conclusion shares the ways teachers and teacher educators can conceptualize the work on teaching-as-human-interaction and use it to improve the teaching perception"--